You are suppose to subtract making it
X+7=13
-7=-7
______
X=6
Your second equation has 2 x-intercepts because its curve goes beneath the x-axis, meaning it crosses the x-axis twice. Your first equation has only one x intercept because its vertex touches the x-axis. The transformation that occurred was a vertical shift downwards, (since the image function has that little -7 at the end : ) )
Represent 'a number' by x
7 times x equals 9 more than 4 times x
7 times x=9+4 times x
7x=9+4x
subtract 4x from both sides
3x=9
divide 3
x=3
the number is 3
Step-by-step explanation:
Here we are given that , the Value of
And we need to find the prove that ,
We know a identity as ,
On cubing both sides of the given equation,
Simplify and then substitute ,
Hence Proved !
Answer:
<em>Pizza eaten together: 5/6,</em>
<em>Pizza left over: 1/6</em>
Step-by-step explanation:
~ If Ellen ate 2/4th of the pizza and John ate 1/3 of the pizza, provided that the pizza counts as a whole ( 1 )... ~
1. Let us simplify 2/4th to be ⇒ 1/2, through simple algebra
2. To see how much they ate together we would neglect that the pizza counts as a whole but simply add 1/2 by 1/3rd.
3. Through simple algebra: 1/2 + 1/3 = 3/6 + 2/6 = <em>Pizza eaten together: 5/6</em>
4. Now to find out how much pizza was left over, we would need the fact that a pizza ⇒ 1 whole. It would be that 1 - 1/2 - 1/3 ⇒ Pizza left over, through the <em>Partition Postulate. </em>In fact, the pizza left over would simply be 1 whole - the pizza eaten together ( 5/6 ).
5. Through algebra: 1 - 1/2 - 1/3 = 1 - 5/6 = <em>Pizza left over: 1/6</em>